ENGLISH TERMS OF INTERNATIONAL FINANCIAL REPORTING STANDARDS IN SPEECH - Nurmamatova Farangiz (TADQIQOTLAR.UZ, 2024)
Annotation: this article provides information about the English terms of International Financial Reporting standards in speech